Use of Prophylactic Antibiotics in Clean Surgical Operations: A Clinical Trail in Ibn-Sina Teaching Hospital in Mukalla, Yemen - Batarfi, Ali Mohammad (Journal of the Faculty of Medicine Baghdad, 2008)
This is a randomized controlled clinical trial carried out to assess the necessity of the use of prophylactic antibiotics for clean surgical operations in the surgical wards of Ibn-Sina teaching hospital during the period from December 2002 to April 2003. A total of 80 patients with clean surgical operations and eligible for the study were randomly allocatedto either treatment or control group (40 patients in each group). Only 7.5% of patients who were not given antibiotics postoperatively developed wound infection while none of the control group, without statistical significance (P>0.05). Neither age nor sex have statistical significant association (P>0.05). All the surgical wound infections were observed in patients were operated for inguinal hernia. The study concluded that use of postoperative prophylactic antibiotic is not necessary for wound healing in case of clean surgical operations except for hernia operations.